1992
DOI: 10.1080/00071669208417445
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucine requirements of the chicken: The effect of excess leucine and valine on the response to isoleucine

Abstract: 1. Three experiments were designed to determine the response of broiler chickens to dietary isoleucine, and to quantify the antagonistic effects of excess leucine and valine on this response. 2. A dilution technique was used to measure the responses in growth rate and food intake to a range of diets differing in their isoleucine concentrations. A summit diet was formulated to contain isoleucine at 1.14 times the requirement and with leucine (1.76 times the requirement) and valine (1.87 times the requirement) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 7 publications
2
28
0
1
Order By: Relevance
“…Indeed, Burnham et al (1992) reported that in case of diet isoleucine content is below the needs of poultry, the high levels of leucine and valine adversely affect the weight gain. Relatively large excesses of leucine and of valine, or of both do not depress growth, because if the dietary content of isoleucine is sufficient to meet the requirements of the broiler (Burnham et al, 1992;Ospina-Rojas et al, 2014). These suggestions indicate that each of amino acid in our BCAA blend was not below the needs of embryo or not excess any one of these amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Burnham et al (1992) reported that in case of diet isoleucine content is below the needs of poultry, the high levels of leucine and valine adversely affect the weight gain. Relatively large excesses of leucine and of valine, or of both do not depress growth, because if the dietary content of isoleucine is sufficient to meet the requirements of the broiler (Burnham et al, 1992;Ospina-Rojas et al, 2014). These suggestions indicate that each of amino acid in our BCAA blend was not below the needs of embryo or not excess any one of these amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our results indicate that the nutrient contents of eggs used in the present trial was in ideal levels, which could not affect the hatchability, chick quality and the degree of growth promotion. It is known that well-nourished, healthy chicks do not respond to in ovo supplements (Schulte-Drüggelte, 2015) and the degree of limiting protein synthesis of these amino acids depend on the ratios and antagonistic relationship between each of these amino acids Burnham et al, 1992) and the protein content and quality of poultry diets (Corzo et al, 2009(Corzo et al, , 2010Ospina-Rojas et al, 2014). Indeed, Burnham et al (1992) reported that in case of diet isoleucine content is below the needs of poultry, the high levels of leucine and valine adversely affect the weight gain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the objectives of this study, 270 lines of broiler chick dose responses (ADG and FE) to protein and BCAA were extracted from the literature, comprising experiments conducted during 1990Á2013 Thomas 1990, 1992;Barbour and Latshaw 1992;Burnham et al 1992;Waldroup et al 2002;Farran et al 2003;Yamazaki et al 2006;Tavernari et al 2013). The dietary levels of protein, isoleucine, leucine, and valine (g kg (1 of diet) were considered as input variables, while ADG and FE were the variables of interest for model output.…”
Section: Materials and Methods Data Sourcementioning
confidence: 99%
“…A probable reason for this is that at the highest protein level the ratio of energy : protein was below the threshold of 73 MJ ME/kg digestible CP required to ensure maximal efficiency of utilisation of the protein Emmans, 1992a and1992b). When feed Val content dropped below 8.3 g/kg, the resultant sharp decrease in feed intake can be ascribed to the combined effect of an imbalance between that nutrient and energy and a reduced growth rate (Burnham et al, 1992). Higher energy levels should be used in the future when such high dietary protein levels are used in the summit feeds.…”
Section: Discussionmentioning
confidence: 99%